Pengaruh Hutang Usaha dan Modal Kerja Terhadap Profitabilitas pada Perusahaan Sub Sektor Perdagangan Eceran yang Terdaftar di Bursa Efek Indonesia (BEI) tahun 2017-2021 - Aurifah, Esti Marina; Carmidah, Carmidah (Budgeting: Jurnal Akuntansi Syariah, 2024)
A single paragraph of about 250 words maximum. For research articles, abstracts should The company's ability to generate profits is closely related to the funding sources used to support business activities. Funding sources can come from external or internal sources. The main objective of this study is to determine the effect of accounts payable and working capital on projected profitability using Return On Assets (ROA). The study was conducted on 8 retail trade sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021 with data collection using documentation techniques and statistically tested using multiple linear regression analysis. The results of the study showed that accounts payable partially had a negative effect on ROA and working capital partially had no effect on ROA. While simultaneously accounts payable and working capital had an effect on profitability represented by ROA in retail trade sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021.